'I'd worry about how to teach it': British values in English classrooms. Issue 3 (26th May 2016) - Maylor, Uvanney
Abstract: What is meant by fundamental British values? How are they constructed and can they be taught in schools? In trying to address these questions, this paper revisits a small-scale research study commissioned by the UK's previous New Labour government. The research was concerned to understand the extent to which schools delivered a diverse curriculum (reflecting the composition of Britain as an ethnically diverse society) as well as teacher and student conceptions of British values and contentions of shared British identities which could be explored in schools as part of the secondary citizenship curriculum. Drawing on interviews with teachers and head teachers in six case study schools across England, this paper examines school and government conceptions of shared 'British' values. It explores how current government promotion of British values is embedded in sociopolitical historical contexts in Britain. Using social construction theory, the paper aims to challenge conceptions of British values being shared by teachers. The paper examines the implications of this for initial teacher education given that qualifying teachers standards require teachers not to undermine British values, yet some teachers do not buy into contentions of British values, and consequently worry about how to teach them. The teacher discourses highlighted also present challenges for teacher education in developing teacher understanding and practice, especially where student teachers bring uninformed views about particular ethnic groups to the classroom.